Do investors care about corporate taxes? - Brooks, Chris; Godfrey, Chris; Hillenbrand, Carola; Money, Kevin (Journal of Corporate Finance, 2016)
This paper conducts a comprehensive examination of the link between corporation tax payment and financial performance in the UK. We find no discernible link between tax rates and stock returns for the UK, no matter how tax payment is measured. This is true throughout the sample period and for both customer-facing and non-customer-facing companies. However, allowing for industry norms and a host of firm characteristics, companies with lower effective tax rates have significantly higher levels of stock market risk. Firms that are reported in the newspapers in a negative way in relation to their level of corporation tax payment experience small negative stock returns, which are partially reversed within a month. However, the initial negative effects and subsequent rebound are both more pronounced for smaller companies. News announcements of the potential involvement of a firm in a corporate inversion (expatriation) result in steeper and much longer-lasting falls in share prices, whereas news stories of a more general nature relating to a firm's tax avoidance or tax payments have little noticeable effect.